Bioelectrochemical cell (BeCC) integrated with granular activated carbon (GAC) in treating spent caustic wastewater: effects of solid retention time (SRT) and organic loading rate (OLR) - Norsafiah, Fazli; N S, A Mutamim; S A, Rahim (IOP Publishing Ltd, 2021)
The study aims to treat spent caustic wastewater by using a bioelectrochemical cell (BeCC) integrated with Granular Activated Carbon (GAC) as the bacterial attachment medium. BeCC is a bioelectrochemical reactor which employs microorganisms for substrates degradation and has the capacity to produce energy simultaneously. Microbial Fuel Cell (MFC) is also known as the bioreactor that could treat wastewater while producing energy. However, the BeCC reactor in the present study is more cost effective than an MFC reactor, since the BeCC was operated without the employment of a proton exchange membrane (PEM). The reactor was operated in a hybrid of anoxic and aerobic conditions whereby a baffle is used as the separator to minimize the oxygen transfer from the cathodic to the anodic side of the reactor. For enhancement of the BeCC performance, 10 g of suspended GAC was added into the BeCC reactor. The use of the suspended GAC is to allow higher surface area available for bacteria attachment. The study determined the best operating solid retention time (SRT) and organic loading rate (OLR) of BeCC in treating spent caustic wastewater and its performance throughout 30 days of operation was evaluated based on its Chemical Oxygen Demand (COD) removal and open circuit voltage (OCV). For SRT study, BeCC was tested at various SRT of range within 10 to 30 days whereas for OLR study, BeCC was tested at various OLR of range within 700 to 900 mg COD /L.d. From the study, the highest COD removal were 94.17% and 92.7% achieved at SRT of 30 days and OLR of 700 mg COD/L.d respectively. Whereas for energy recovery, the highest OCV were 336.4 mV and 362 mV achieved at SRT of 20 days and OLR of 800 mg COD/L.d respectively. Biochemical bacteria identification test was also carried out to identify the bacteria morphology attached on GAC in the BeCC at SRT of 20 days with 700 mg COD/ L.d of OLR and it is found that Klebsiella Oxytoca was the dominant bacteria attached on the GAC.